2021
DOI: 10.3390/healthcare9030252
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anxiety Levels of Nursing Students Because of e-Learning during the COVID-19 Pandemic

Abstract: The continued expand of the coronavirus disease 19 (COVID-19) pandemic, confinement measures and an urgent change in the education of nursing students from traditional education to distance learning throughout the country affect the mental health of university students. This study analyzed state-trait anxiety levels of nursing students because of e-Learning during two periods of the COVID-19 confinement. A mixed follow-up study was used, which evaluates the same cohort cross-sectionally but with a longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 28 publications
4
34
1
1
Order By: Relevance
“…Considering that more than half of the students were attending courses related to heath science such as physical education, coach or physiotherapy, those results could be compared to students of medical studies. Results of students from this study are similar to those of German medical students, with a mean of 45.12 [30], dentistry students from Turkey with a mean score of 49.96 for females and 50.26 for males [31] or Spanish nursing students with scores exceeding a mean of 50 points [32]. Students of non-health related curriculums also had elevated STAI results, whereas Turkish female students had mean scores of 45.28 and males of 41.29 points [33]; Italian students had a mean score of 49.8 points [34].…”
Section: Discussionsupporting
confidence: 69%
“…Considering that more than half of the students were attending courses related to heath science such as physical education, coach or physiotherapy, those results could be compared to students of medical studies. Results of students from this study are similar to those of German medical students, with a mean of 45.12 [30], dentistry students from Turkey with a mean score of 49.96 for females and 50.26 for males [31] or Spanish nursing students with scores exceeding a mean of 50 points [32]. Students of non-health related curriculums also had elevated STAI results, whereas Turkish female students had mean scores of 45.28 and males of 41.29 points [33]; Italian students had a mean score of 49.8 points [34].…”
Section: Discussionsupporting
confidence: 69%
“…Turkish students reveals state anxiety level ranging from 42 to 46.3 points [32], which is lower than the participants of this study. Similarly nursing students from Spain showed anxiety levels which ranged from 50 to 58 points [33], which was concurrent with presented results. Similar results were also obtained from the students in China [34].…”
Section: Discussionsupporting
confidence: 90%
“…A survey conducted by Aftab et al [32] among undergraduate and postgraduate students studying medicine worldwide found a prevalence of depression of 41.5% in these students, which is dramatically higher than that found this study; however, anxiety among those students was less prevalent than among those in this study. These studies reveal a higher degree of anxiety among college students during the COVID-19 outbreak, and web-based learning is an important cause of increased anxiety and depression [33][34][35].…”
Section: Principal Findingsmentioning
confidence: 98%